A static analysis of I/O characteristics of scientific applications in a production workload - Pasquale, B. K.; Polyzos, G. C. (Proceedings of the 1993 ACM/IEEE conference on Supercomputing, 1993)
Past research on high performance computers for scientific applications has concentrated on CPU speed and exploitation of parallelism, but has, until very recently, neglected I/O considerations. This paper presents a study of the production workload at the San Diego Supercomputer Center from an I/O requirements and characteristics perspective. Results of the analyses support the hypothesis that a significant proportion of I/O intensive, long running, frequently executed scientific applications have predictable I/O requirements.